The relevance and scenarios of pedagogical supervision in the face of hybrid teaching in the COVID-19 pandemic context in Tocantins (Research, Society and Development, 2021)
The objective of this work was to verify, through a bibliographical and documentary research, the role of the pedagogical supervisor during remote teaching during the period of the COVID-19 pandemic. Furthermore, descriptive and exploratory research, deductive method and a qualitative approach were used in the methodology. At first, it seeks to describe the profile of this professional and how he/she acts in meeting the teaching proposal, planning of teachers linked to meaningful student learning. In the second moment, the Hybrid Teaching Proposal of the State Education Network of the State of Tocantins will be analyzed in the perspective that involves Information and Communication Technologies (ICTs), as methodological tools for the advancement of education, contributing to access, permanence and student success at school. The survey results show that, in this pandemic process, the State Secretariat for Education, Youth and Sports (Seduc) implemented public policies, through the Plan for the resumption of classroom activities-hybrid teaching, to guide and strengthen the teaching work, through the technical support of the pedagogical supervision, with a view to welcoming and motivating the team, articulating with the families a new educational process, where, in fact, everyone is involved for the success of the students. Finally, the supervisor's role makes the difference for a dialogic education based on the relationship of dialogue and participation.